The evolution of orientalism / Haitham Ibrahim Ahmad al-Sharu, Salmah Ahmad and Muhammad Nur Abdullah - Ahmad al-Sharu, Haitham Ibrahim; Ahmad, Salmah; Nur Abdullah, Muhammad (Academy of Contemporary Islamic Studies, 2016)
This study seeks to release the evolution of Orientalist movement and modern methods in the process of Orientalism and comparing the old ways or methods. The study aims to put readers to the true image of the process of Orientalism, and it did not end with the passage of time and change the nomenclature and the different ways and methodology, With the assistance of the most important sources and references from Arab and some foreign and Western sources translated into Arabic, and the statement of the difference between the process of Orientalist oriented intellectual movement purely scientific. In all this it is paving the way for researchers and readers to distinguish between pure scientific movement and intended purposes and absorb riddled with problems. The study was of the view that the time has come for the advancement of a comparative study to clarify the basic end of the process of studying the legacy of the Middle linguistic and literary and Islamic religion. And so what we found during search of the different end of the process of studying the Middle heritage between the Orientalists, and between those who follow the opinions of the Arabs on the other hand in fairness science and history and civilization of the East. For example, not limited to take a section of the Orientalists allegedly Mncefon they are few, such as Hadrian Ryland and Johan G and Gustan Le Bon. And non Mncefon and haters of Almstcherqaan and they are many, such as David Samuel Margoliouth Orientalist a Jewish fanatic, and even Flip a Lebanese Christian, an American citizen, and Henri Lammens French Jesuit spiteful.